Endoglucanase and β-glycosidase activities in an evergreen oak litter: annual variation and regulating factors - Criquet, S.; Tagger, S.; Vogt, G.; Le petit, J. (Soil Biology and Biochemistry, 2002)
This paper represents the third part of a larger study about the processes involved in litter biodegradation in an oak copse in France. It concerns the variations in activities of endoglucanases and of β-glycosidases over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Q. ilex is the most abundant tree species in forests of the French Mediterranean area. The activities of several endoglucanases and β-glycosidases, and the concentrations of the proteins and reducing sugars were measured in the evergreen oak litter between October 1997 and October 1998. Several biotic and abiotic factors, potentially involved in the regulation of the activities of these hydrolyzing enzymes, were also measured: culturable heterotrophic bacteria, cellulolytic bacteria and cellulolytic fungi, moisture, temperature and pH of the litter. Under this Mediterranean climate, the moisture of the litter was strongly correlated with many factors and is likely to be important in regulating the temporal dynamics of various biological parameters. A multiple regression analysis showed that the annual dynamic of the culturable heterotrophic bacteria was primarily influenced by moisture but also by variations in concentration of reducing sugars in the litter. Moreover, these bacteria were correlated with the activities of several β-glycosidases, and specifically with the N-acetyl-glucosaminidases (r=0.93). No relationships were established between the number of cellulolytic microorganisms (bacteria and fungi) and the activities of endoglucanases (i.e. cellulases and hemicellulases). The seasonal trends of certain biotic processes, and the influence of pH and of temperature on these processes are also discussed. Electrophoretic analyses were used to estimate the number of cellulase and xylanase isoenzymes in the litter, and to study their fluctuations over one year. The prevailing cellulase isoenzyme had a Rf of 0.64, and there was no relationship between the abundance of cellulolytic microorganisms and the electrophoretic profiles of the cellulases. In the case of the xylanases, the electrophoretic profiles were homogenous throughout the year, and the prevailing xylanase had a Rf of 0.75.
Keywords: Cellulase; hemicellulase; Isoenzymes; litter; Polysaccharides

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees